Cement composition and method thereof

JP2024509961A5Inactive Publication Date: 2025-03-13UNIVERSITY OF MAINE +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023555556
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-03-12
Filing Date
2022-03-11
Publication Date
2025-03-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Cement compositions face issues with chemical and physical degradation due to water absorption, leading to durability problems such as D-cracking, spalling, and steel corrosion, and traditional methods to reduce water absorption are costly and ineffective in marine environments.

Method used

Incorporating modified biochar with a hydrophobic agent into cement compositions to enhance hydrophobicity and electrical conductivity, reducing water absorption and improving stress-strain monitoring capabilities.

Benefits of technology

The modified biochar compositions exhibit lower water absorption, increased electrical conductivity, and enhanced durability, allowing for real-time stress-strain monitoring while reducing the carbon footprint and production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present disclosure provides compositions, including modified biochar and cement compositions, as well as methods for making and characterizing such compositions, and / or techniques relating to such compositions, their manufacture and / or their uses.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to and the benefit of U.S. Provisional Application No. 63 / 160,397, filed March 12, 2021, the disclosure of which is incorporated by reference in its entirety herein. [Background technology]

[0002] Cement is a binder, a construction substance that sets, hardens, and adheres to other materials, binding them together. Cement is typically mixed with sand and gravel (aggregates). Cement is mixed with fine aggregate to produce mortar for masonry, or with sand and gravel to produce concrete. Concrete is one of the most widely used materials. Summary of the Invention [Means for solving the problem]

[0003] The present disclosure provides compositions comprising cement compositions and biochar, as well as methods of making and using such compositions; the present disclosure also provides various techniques for making, using and / or characterizing such compositions.

[0004] Among other things, the present disclosure identifies the source of at least one problem in certain compositions, including cement compositions. Alternatively, or in addition, according to various embodiments, the provided technology provides certain advantages and / or overcomes one or more problems associated with the prior art.

[0005] In some embodiments, the present disclosure provides techniques for improving certain properties of biochar and / or compositions comprising biochar. In some embodiments, compositions comprising biochar according to the present disclosure (e.g., cement composition(s) comprising biochar) exhibit increased hydrophobicity (e.g., compared to cement compositions not comprising biochar). In particular, the present disclosure provides techniques that may be particularly suitable and / or may provide certain advantages for mitigating chemical and physical degradation of the composition, e.g., by reducing water absorption.

[0006] In some embodiments, compositions including biochar according to the present disclosure exhibit increased electrical conductivity (e.g., compared to cement compositions not including biochar). Among other things, the present disclosure therefore provides techniques that may be particularly suitable and / or may offer particular advantages for use in real-time metrological monitoring of stress-strain in compositions, e.g., by measuring electrical resistivity measurements.

[0007] In one aspect, the present disclosure provides a composition comprising at least one cement composition and a modified biochar comprising biochar and a hydrophobic agent (e.g., more hydrophobic than biochar).

[0008] In some embodiments, the modified biochar is more hydrophobic than the biochar.

[0009] In some embodiments, the composition is piezoresistive (eg, the composition is characterized by having a linear correlation between applied stress and change in resistivity).

[0010] In some embodiments, the composition comprises modified biochar in the range of 1% to 30% by weight of the combination of the cement composition and the modified biochar.

[0011] In some embodiments, the hydrophobic agent is selected from the group consisting of stearic acid, oleic acid, myristic acid, and combinations thereof.

[0012] In some embodiments, the mass ratio of hydrophobic agent to biochar is in the range of about 1:100 to 1:10.

[0013] In some embodiments, the composition further comprises water.

[0014] In some embodiments, the weight ratio of water to the combination of cement composition and modified biochar is about 0.25 to 0.8.

[0015] In some embodiments, the composition further comprises fine aggregate.

[0016] In some embodiments, the mass ratio of the combination of the cement composition and the modified biochar to the fine aggregate is about 2-3.

[0017] In some embodiments, the composition has a lower (e.g., about 1% to 25% lower) compressive strength compared to a cement composition (or a composition that includes a cement composition but does not include modified biochar).

[0018] In some embodiments, the composition has a lower (e.g., about 1% to 20% lower) flexural strength compared to a cement composition (or a composition that includes a cement composition but does not include modified biochar).

[0019] In some embodiments, the composition has a higher (e.g., about 1% to 20% higher) heat release (e.g., per gram of cement composition) than the cement composition (or a composition that includes the cement composition but does not include the modified biochar).

[0020] In some embodiments, the composition comprises less (e.g., about 1% to 10% less) chemically bound water (e.g., per gram of cement composition) than a cement composition (or a composition that comprises a cement composition but does not include modified biochar).

[0021] In some embodiments, the composition contains less (e.g., about 1% to 50% less) Ca(OH)2 than the cement composition (or a composition that contains the cement composition but does not contain the modified biochar).

[0022] In some embodiments, the composition has a lower (e.g., about 1% to 95% lower) flow index than a cement composition (or a composition that includes a cement composition but does not include modified biochar).

[0023] In some embodiments, the composition has a lower (e.g., about 1% to 90% lower) water absorption rate than a cement composition (or a composition that includes a cement composition but does not include modified biochar).

[0024] In some embodiments, the composition has a higher (e.g., about 1% to 40% higher) electrical conductivity than a cement composition (or a composition that includes a cement composition but does not include modified biochar).

[0025] In some embodiments, the average dimension of the modified biochar is in the range of 1-50 μm.

[0026] In some embodiments, the average size of the cement composition is in the range of 1 to 50 μm.

[0027] In some embodiments, the modified biochar comprises carbon (eg, about 80% by weight), hydrogen (eg, about 1% by weight), and nitrogen (eg, about 0.2% by weight).

[0028] In some embodiments, the composition is a paste or mortar.

[0029] In another aspect, the disclosure provides a method, comprising preparing a modified biochar by combining biochar with a hydrophobic agent, the modified biochar being more hydrophobic than the biochar; and further comprising combining a cement composition with the modified biochar to form a composition.

[0030] In some embodiments, biochar is prepared by pyrolysis of wood chips.

[0031] In some embodiments, the hydrophobic agent is mixed after pyrolysis.

[0032] In some embodiments, the biochar is pulverized in the presence of a hydrophobic agent.

[0033] In some embodiments, the mass ratio of hydrophobic agent to biochar is in the range of about 1:100 to 1:10.

[0034] In some embodiments, the biochar is pulverized by using a mortar and pestle.

[0035] In some embodiments, the method further comprises adding water to the composition.

[0036] In some embodiments, the composition is piezoresistive (eg, the composition is characterized by having a linear correlation between applied stress and change in resistivity).

[0037] In some embodiments, the composition comprises modified biochar in the range of 1% to 30% by weight of the combination of the cement composition and the biochar.

[0038] In some embodiments, the hydrophobic agent is selected from the group consisting of stearic acid, oleic acid, myristic acid, and combinations thereof.

[0039] In another aspect, the disclosure provides a composition produced by one or more of the methods described herein.

[0040] In another aspect, the disclosure provides a method of making a mortar for construction, comprising: preparing biochar using pyrolysis; preparing a modified biochar by mixing the biochar with a hydrophobic agent, the hydrophobic agent comprising stearic acid, the modified biochar comprising about 2% to about 20% by weight of the hydrophobic agent, and preparing the modified biochar comprises pulverizing the biochar and the hydrophobic agent (e.g., for about 1 hour to about 5 hours); combining a cement composition with the modified biochar to create a binder, the modified biochar comprising about 1% to about 30% by weight of the cement composition and modified biochar combination; adding water to the binder in a water to binder weight ratio of about 0.25 to 0.8; adding fine aggregate to the binder in a fine aggregate to binder weight ratio of about 2 to 3; and mixing the water, fine aggregate, and binder to produce a mortar.

[0041] In another aspect, the disclosure provides a construction mortar comprising at least one cement composition; modified biochar comprising biochar and a hydrophobic agent, wherein the hydrophobic agent comprises stearic acid, the modified biochar comprises about 2% to about 20% by weight of the hydrophobic agent, the modified biochar has an average dimension in the range of 1-50 μm, and the modified biochar comprises about 1% to about 10% by weight of a total weight of the combination of the at least one cement composition and the modified biochar; and further comprising water, wherein the mortar is characterized in that the composition is piezoresistive, and the composition is characterized in that the composition has a water absorption rate that is 1% to 90% lower than the at least one cement composition (or a composition comprising the at least one cement composition but not the modified biochar).

[0042] The drawings, consisting of at least the following figures, are intended for purposes of illustration only and not limitation: [Brief description of the drawings]

[0043] [Figure 1]Included are exemplary optical and scanning electron microscopy (SEM) images of biochar, modified biochar, and compositions according to the present disclosure that include cement compositions and modified biochar.

[0044] [Diagram 2] 1 is a graph showing exemplary particle size distributions of cement compositions and modified biochar.

[0045] [Diagram 3] 1 illustrates an exemplary setup for measuring the rate of change of resistivity (FCR) of a sample under three-point bending conditions.

[0046] [Figure 4A] 1 is a graph showing exemplary heat flow per gram of cement composition (mW / g) as a function of time.

[0047] [Figure 4B] 1 is a graph showing exemplary gross heat release per gram of cement composition (J / g) as a function of time.

[0048] [Figure 4C] FIG. 1 is a graph showing exemplary heat flow per gram (mW / g) as a function of time for both cement compositions and modified biochar.

[0049] [Figure 4D] FIG. 1 is a graph showing exemplary gross heating value per gram (J / g) as a function of time for both cement compositions and modified biochar.

[0050] [Figure 4E] 1 shows exemplary changes in heat flow per gram (mW / g) after hydration over 100 hours for both the cement composition and modified biochar.

[0051] [Figure 4F]Illustrates exemplary changes in total heat production per gram (J / g) after hydration over 100 hours for both cement compositions and modified biochar.

[0052] [Diagram 5] 1 shows exemplary thermogravimetric plots of paste samples containing different amounts of modified biochar.

[0053] [Figure 6A] 1 shows an exemplary graph depicting chemically bound water per gram after 7, 14 and 28 days of curing for both cement composition and modified biochar.

[0054] [Figure 6B] 1 shows an exemplary graph depicting Ca(OH)2 per gram after 7, 14 and 28 days of curing for both cement composition and modified biochar.

[0055] [Figure 7A] 1 shows exemplary Fourier transform infrared spectroscopy (FTIR) spectra of unmodified and modified biochar.

[0056] [Figure 7B] 1 shows exemplary FTIR spectra of a cement composition and a composition including modified biochar after hydration for 28 days.

[0057] [Figure 8] 1 is a graph showing exemplary flow indexes of compositions having different modified biochar contents. Data labels indicate the percentage decrease in flow index due to the addition of modified biochar. Error bars represent one standard deviation.

[0058] [Figure 9](A) is a graph showing the compressive strength of exemplary compositions with different modified biochar contents. (B) is a graph showing the flexural strength of exemplary compositions with different modified biochar contents. Data labels indicate the percentage variation in strength with the addition of modified biochar relative to a control batch (e.g., no modified biochar). Error bars represent one standard deviation.

[0059] [Figure 10] FIGS. 3A-3C are exemplary SEM images at different magnification levels showing a cement composition and a composition comprising modified biochar.

[0060] [Figure 11] Figures A-C show exemplary water uptake measurements, percentage reduction in initial water uptake, and percentage reduction in secondary water uptake versus the square root of time for various modified biochar content, respectively. Data labels indicate the percent change in water uptake due to the addition of modified biochar.

[0061] [Figure 12] 1 is a graph showing the electrical conductivity of exemplary compositions with various modified biochar contents. Error bars represent one standard deviation.

[0062] [Figure 13] Graphs A and B show the percent change in resistivity (FCR) for a composition containing 0% modified biochar (i.e., control batch) and a composition having 15% modified biochar, respectively.

[0063] [Figure 14] A and B show exemplary CO2 sequestration / reduction in cement-based materials when modified biochar is applied as a partial replacement for cement. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0064] definition In this application, unless otherwise clear from the context, (i) the term "a" may be understood to mean "at least one"; (ii) the term "or" may be understood to mean "and / or"; (iii) the terms "comprising" and "including" may be understood to include the recited components or steps; (iv) the term "about" may be understood to allow for standard deviation that would be appreciated by one of ordinary skill in the art; and (v) when ranges are provided, the endpoints are included.

[0065] About: The term "about", when used herein with respect to a value, refers to a value that is in the same order of magnitude with respect to the value referenced. In general, a person skilled in the art familiar with the context will recognize the reasonable degree of variation encompassed by "about" in that context. For example, in some embodiments, the term "about" may encompass a range of values ​​that are within 25%, 20%, 19%, 18%, 17%, 16%, 15%, 14%, 13%, 12%, 11%, 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1% or less of the value referenced.

[0066] Agent: As used herein, the term "agent" may refer to an entity or phenomenon. In some embodiments, an agent may be characterized by a particular feature and / or action. In some embodiments, an agent may be any chemical class of compound, molecule, or entity, including, for example, a small molecule, a polypeptide, a nucleic acid, a sugar, a lipid, a metal, or a combination or complex thereof. In some embodiments, the term "agent" may refer to a compound, molecule, or entity that includes a polymer. In some embodiments, the term may refer to a compound or entity that includes one or more multimeric moieties. In some embodiments, the term "agent" may refer to a compound, molecule, or entity that is substantially free of a particular polymer or multimeric moiety. In some embodiments, the term may refer to a compound, molecule, or entity that is free or substantially free of any polymer or multimeric moiety. In some embodiments, an agent may be or include a system or device. In some embodiments, an agent may be or include a force, e.g., an electrical force, a gravitational force, a magnetic force, etc.

[0067] Biochar: As used herein, the term "biochar" refers to a carbon-rich solid material. In some embodiments, biochar is formed by pyrolysis of biomass (e.g., by heating biomass in an oxygen-free or low-oxygen environment such that it does not burn (or only partially burns)). In some embodiments, biochar is formed by acid hydrolysis and dehydration or hydrothermal treatment of biomass. Biochar is sometimes also referred to as hydrochar.

[0068] Biomass: As used herein, the term "biomass" refers to any cellulosic or lignocellulosic material, including materials that contain cellulose and / or lignocellulose and optionally further contain hemicellulose, lignin, starch, oligosaccharides, and / or monosaccharides. Biomass may also contain additional components, such as proteins and / or lipids. Biomass may be from a single source, or biomass may include mixtures from more than one source, for example, biomass may include a mixture of corn cobs and corn stover, or a mixture of grass and leaves. Biomass includes, but is not limited to, bioenergy crops, agricultural residues, municipal solid waste, industrial solid waste, paper sludge, yard waste, waste wood and forestry waste, or combinations thereof. Examples of biomass include, but are not limited to, corn grains, corn cobs, crop residues such as corn husks, corn stover, grass, wheat, wheat straw, barley, barley straw, hay, rice straw, switchgrass, waste paper, sugarcane bagasse, sorghum, soybeans, parts obtained from grain milling, trees, branches, roots, leaves, wood chips, sawdust, shrubs and bushes, vegetables, fruits, flowers, and animal manure, or combinations thereof. In one embodiment, particularly useful biomass includes biomass that has a relatively high carbohydrate value, is relatively dense, and / or is relatively easy to collect, transport, store, and / or handle. In some embodiments, useful biomass includes corn cobs, corn stover, sawdust, and sugarcane bagasse. The term "biomass" may also include (i) waste materials, including animal manure, such as poultry waste; (ii) commercial or recycled materials, including plastic, paper, paper pulp, cardboard, sawdust, wood residues, wood shavings, and cloth; (iii) municipal waste, including sewage waste; (iv) agricultural waste, such as coconut shells, pecan shells, almond shells, coffee grounds; and (v) crop feed, such as rice straw, wheat straw, rice husks, corn stover, corn straw, and corn cobs.

[0069] Cement Composition: As used herein, the term "cement composition" refers to a binder that is a construction substance that sets, hardens, and adheres to other materials to bind them together. In certain embodiments, cement may be utilized to bind sand and gravel (aggregates). In certain embodiments, cement mixed with fine aggregate produces mortar for masonry construction. In certain embodiments, cement mixed with sand and gravel produces concrete. Cements used in construction are typically inorganic, often lime-based or calcium silicate-based, and may be characterized as either hydraulic or non-hydraulic depending on the cement's ability to set and harden in the presence of water.

[0070] Hydrophilic: As used herein, the terms "hydrophilic" and / or "polar" may refer to a tendency to be miscible with water, to dissolve readily in water, or to be wetted by water. In some embodiments, hydrophilicity is measured by contact angle measurements between water and a solid surface using techniques that will be understood by those of skill in the art. In some embodiments, a hydrophilic material has a contact angle between water and a surface that is less than 90°.

[0071] Hydrophobicity: As used herein, the terms "hydrophobic" and / or "non-polar" may refer to a tendency to repel (not associate with) water or not readily dissolve in water. In some embodiments, hydrophilicity is measured by contact angle measurements between water and a surface using techniques that will be understood by those of skill in the art. In some embodiments, hydrophilic materials are identified as those that have a contact angle between water and a surface that is greater than 90°.

[0072] Pyrolysis: As used herein, the term "pyrolysis" refers to the thermochemical decomposition of organic materials at high temperatures in an environment with limited amounts of oxidizing agents or in the absence of oxidizing agents such as oxygen. In some embodiments, the temperature and rate of temperature change vary depending on the type of biomass being treated, the desired products, etc. Pyrolysis produces primarily water, syngas, light organic compounds, heavy organic compounds, and biochar. In some embodiments, some of the organic compounds are acids. Sometimes, other acids of non-organic nature are obtained from the pyrolysis process. In certain embodiments, acids such as hydrogen chloride are by-products of the pyrolysis of biomass.

[0073] Detailed Description The following description is merely for illustrating and illustrating the present disclosure, and is not intended to limit the present disclosure to the specific embodiments described herein.Unless otherwise specified, scientific and technical terms have the same meaning as commonly understood by those skilled in the art to which this disclosure belongs.All references cited herein, including patent applications and publications, are incorporated by reference in their entirety.

[0074] Cement-based concrete infrastructures often exhibit durability-related damage (e.g., D-cracks, spalling, scaling, and rebar corrosion) earlier than expected. Water can be a significant factor in these chemical and physical deterioration processes of cementitious composites. The physical and / or chemical phenomena associated with water transport in porous cementitious materials can be related to their permeability. For example, water in cementitious composites reacts and evaporates during the curing process, resulting in the formation of capillary pores. Liquids and gases can penetrate through these capillaries into the concrete matrix with or without pressure. Water sorption (including absorption and adsorption) can lead to the introduction of harmful ions (e.g., chloride salts, sulfate salts, etc.) into the hydrated cement composition. The ions can cause the matrix to lose its chemical stability. Thus, the durability performance of a cement composition is affected by its permeability. By reducing the permeability or water sorption, the resistance of the cement composition to the penetration of harmful ions can be improved.

[0075] The water absorption coefficient is useful in predicting the service life of concrete (e.g., including cementitious compositions) as a structural material. Commercially available permeability reducing admixtures (PRAs) can be used to achieve low water absorption in cementitious compositions. The high cost of PRA has hindered its application in concrete infrastructure. Commercially available PRAs are also known to increase setting time, reduce the strength of concrete mixes, and are less effective in marine environments.

[0076] Stress-strain monitoring can be accomplished by measuring electrical resistance. Conventional cement compositions (e.g., Portland cement) have low electrical conductivity. To monitor stress-strain, it is necessary to add conductive materials to increase the electrical conductivity of conventional cement compositions through various processes (e.g., contact conduction, tunneling effect).

[0077] According to some embodiments, the present disclosure provides methods of preparing certain compositions (e.g., including a cement composition and biochar and / or one or more hydrophobic agents) that may provide sufficient mechanical and chemical stability. In some embodiments, the compositions of the present disclosure may provide distinct or unique properties that may address previously unmet requirements, for example, related to metrological monitoring of stress-strain in the composition.

[0078] The present disclosure is based, in part, on the surprising insight that desirable compositions can be achieved by modifying biochar (e.g., comprising a cement composition and biochar). In some embodiments, the composition comprises biochar (e.g., modified biochar) and a cement composition. In some embodiments, the modified biochar comprises biochar and at least one hydrophobic agent.

[0079] Biochar As will be appreciated by those of skill in the art, biochar can include any of a variety of characteristics suitable for the application. In some embodiments, biochar according to the present disclosure is a material containing high (e.g., greater than 70%) carbon content made by direct thermal decomposition of organic material (e.g., biomass (e.g., wood, agricultural residues, leaves)). In some embodiments, biochar is characterized by its black color and high porosity (e.g., approximately 0.016-0.25 cm2). 3 / g) and lightweight (e.g., about 1.5 to 2 g / cm 3 ), and / or fine particles (e.g., average particle size of about 1 μm to about 1 mm), and / or large surface area (e.g., up to about 490 m 2 / g).

[0080] The present disclosure encompasses the recognition that creating biochar can include any known method. By way of non-limiting example, in some embodiments, biochar can be created by a pyrolysis process. In some embodiments, pyrolysis of biochar is carried out in the absence of oxygen or in substantially low-oxygen conditions. The specific yield from pyrolysis can depend on the process conditions (e.g., temperature, residence time, and heating rate). For example, temperatures between 400-500°C (673-773K) produce more solid products (e.g., biochar), while temperatures above 700°C (973K) favor the production of liquid and gaseous fuel components. Winsley, Peter (2007). "Biochar and bioenergy production for climate change mitigation". New Zealand Science Review. 64. Pyrolysis can occur more quickly (e.g., taking seconds instead of hours) at higher temperatures. In some embodiments, biochar can be created by acid hydrolysis and dehydration. In some embodiments, biochar can be produced by hydrothermal treatment.

[0081] According to various embodiments, biochar can include any known composition suitable for the application. For example, in some embodiments, biochar includes carbon, hydrogen, and nitrogen. In some embodiments, biochar includes carbon in the range of about 75% to about 99%, about 75% to about 95%, about 75% to about 90%, or about 75% to about 85% by weight. In some embodiments, biochar includes hydrogen in the range of about 0.1% to about 5%, about 0.1% to about 3%, about 0.1% to about 2%, about 0.5% to about 2%, or about 1% to about 2% by weight. In some embodiments, biochar includes nitrogen in the range of about 0.05% to about 2%, about 0.05% to about 1%, about 0.05% to about 0.5%, or about 0.1% to about 0.5% by weight.

[0082] Modified Biochar In some embodiments, a modified biochar according to the present disclosure comprises biochar and a hydrophobic agent. In some embodiments, the hydrophobic agent is more hydrophobic than the biochar. In some embodiments, the modified biochar is more hydrophobic than the biochar (e.g., unmodified biochar).

[0083] In some embodiments, hydrophobicity is measured by contact angle measurements. Contact angle is the angle where a liquid-vapor interface meets a solid surface, conventionally measured by a liquid. It quantifies the wettability of a solid surface by a liquid by Young's equation. At a given temperature and pressure, a given system of solid, liquid and vapor has a unique equilibrium contact angle. However, in practice, a dynamic phenomenon of contact angle hysteresis is often observed, ranging from an advancing (maximum) contact angle to a receding (minimum) contact angle. The equilibrium contact angle lies within these values ​​and can be calculated from them. The equilibrium contact angle reflects the relative strength of the liquid, solid and vapor molecular interactions. The theoretical expression of the contact angle comes from the consideration of thermodynamic equilibrium between three phases: liquid phase (L), solid phase (S) and gas or vapor phase (G) (which may be a mixture of the surrounding atmosphere and the equilibrium concentration of liquid vapor). If the solid-vapor interfacial energy is γ SG and the solid-liquid interfacial energy is γSL where the liquid-vapor interfacial energy (i.e., surface tension) is γ LG If the equilibrium contact angle is expressed as C From these quantities, Young's equation is: Gamma SG -γ SG -γ SG cosθ C =0 Equation (1) is determined by.

[0084] In general, a solid surface is considered hydrophilic if the water contact angle is less than 90°, and hydrophobic if the water contact angle is greater than 90°. Highly hydrophobic surfaces made from low surface energy (e.g., fluorinated) materials can have water contact angles as high as about 120°.

[0085] In some embodiments, the water contact angle of the hydrophobic agent is greater than the water contact angle of the biochar. In some embodiments, the water contact angle of the modified biochar is greater than the water contact angle of the biochar (e.g., unmodified biochar). In some embodiments, the modified biochar has a water contact angle greater than 150° (e.g., superhydrophobic).

[0086] Hydrophobic Drugs According to various embodiments, any hydrophobic agent(s) suitable for the application may be used. In some embodiments, a particular composition includes more than one hydrophobic agent (e.g., 2, 3, 4, 5, 6, 7, 8, 9, 10 or more hydrophobic agents). In some embodiments, the hydrophobic agent includes one or more fatty acids. In some embodiments, the hydrophobic agent is a fatty acid, for example, from a series of surfactants graded according to the hydrophilic-lipophilic balance (HLB) scale. In some embodiments, the hydrophobic agent is or includes at least one of stearic acid, oleic acid, myristic acid, and combinations thereof. In some embodiments, the hydrophobic agent includes stearic acid.

[0087] In some embodiments, the modified biochar comprises a hydrophobic agent in a range of about 1% to about 10% by weight, about 1% to about 8% by weight, about 1% to about 6% by weight, or about 2% to about 6% by weight.

[0088] In some embodiments, the hydrophobic agent is associated with the modified biochar. In some embodiments, the hydrophobic agent is incorporated (e.g., by chemical and / or physical interactions) on the surface of the biochar. In some embodiments, the hydrophobic agent is incorporated (e.g., by chemical and / or physical interactions) into the biochar (e.g., within the pores of the biochar). In some embodiments, the hydrophobic agent is incorporated (e.g., by chemical and / or physical interactions) both on the surface and within the pores of the biochar. In some embodiments, the hydrophobic agent is in proximity to the biochar.

[0089] In some embodiments, the method of preparing modified biochar includes mixing biochar with a hydrophobic agent. In some embodiments, mixing can be or include pulverization. In some embodiments, pulverization can be or include grinding, crushing, and / or homogenization. In some embodiments, the biochar and hydrophobic agent are ground. In some embodiments, the biochar and hydrophobic agent are ground for about 1 to about 5 hours, about 1 to about 4 hours, about 2 to about 5 hours, about 2 to about 4 hours, or about 1 to about 3 hours. Without wishing to be bound by any particular theory, the hydrophobic agent may act as a grinding aid. In some embodiments, the biochar and hydrophobic agent are ball milled (e.g., in a planetary ball mill, e.g., at 2520 r / min for 3 hours).

[0090] In some embodiments, the average dimension of the modified biochar is smaller than the average dimension of the biochar (e.g., unmodified biochar). In some embodiments, the average dimension of the modified biochar is in the range of about 1 μm to about 100 μm, about 1 μm to about 50 μm, about 1 μm to about 30 μm, about 1 μm to about 20 μm, or about 5 μm to about 20 μm. In certain embodiments, the particle size of the modified biochar refers to the dimension of the particles of the modified biochar. In certain embodiments, the dimension may refer to the maximum dimension of the particle (e.g., the length of the particle), the average dimension of the particle, or the diameter of the particle. In certain embodiments, the particles may be described as spherical particles having a given dimension. In certain embodiments, the particle size of the particles may be measured using any suitable technique known to one of skill in the art, such as, but not limited to, laser diffraction, dynamic light scattering, imaging, sedimentation, electrophoretic light scattering, or electrochemical sensing zone.

[0091] Cement Composition In some embodiments, the cement compositions according to the present disclosure are building materials that set, harden, and adhere to and bind other materials together, hi some embodiments, the cement compositions may be used to bind sand and gravel, for example.

[0092] In some embodiments, the cement composition is hydraulic (e.g., it can set and become sticky by chemical reaction of dry ingredients with water). In some embodiments, the cement composition is non-hydraulic (e.g., it does not set under wet conditions or in water but reacts with carbon dioxide).

[0093] According to various embodiments, any cement suitable for the application may be used. In some embodiments, the cement composition includes Portland cement (e.g., ordinary Portland cement (OPC), white Portland cement, I, II, II, IV, and / or V type OPC). In some embodiments, the Portland cement is a hydraulic cement produced by powdering a clinker containing hydraulic calcium silicate. In some embodiments, the Portland cement includes CaO, SiO2, Al2O3, Fe2O3, and / or SO3. In some embodiments, the Portland cement includes more than about 50 wt%, about 60 wt%, or about 67 wt% calcium silicate (e.g., 3CaO·SiO2, 2CaO·SiO2). In some embodiments, the Portland cement includes aluminum-containing and iron-containing clinker phases. In some embodiments, the Portland cement includes magnesium oxide (e.g., less than about 5 wt%). In some embodiments, the weight ratio of CaO to SiO2 is less than about 2.0.

[0094] In some embodiments, the cement composition comprises Type I Portland cement (e.g., about 55 wt.% C3S (i.e., (CaO)3·SiO2), about 19 wt.% C2S (i.e., (CaO)2·SiO2), about 10 wt.% C3A (i.e., (CaO)3·Al2O3), about 7 wt.% C4AF (i.e., (CaO)3·Al2O3·Fe2O3), about 2.8 wt.% MgO, about 2.9 wt.% SO3, and about 1.0 wt.% free CaO). In some embodiments, the cement composition comprises less than about 15 wt.% C3A. In some embodiments, Type I is assumed unless another type is specified.

[0095] In some embodiments, the cement composition comprises a Type II Portland cement (e.g., comprising about 51 wt.% C3S, about 24 wt.% C2S, about 6 wt.% C3A, about 11 wt.% C4AF, about 2.9 wt.% MgO, about 2.5 wt.% SO3, and about 1.0 wt.% free CaO). In some embodiments, the cement composition comprises less than about 8 wt.% C3A.

[0096] In some embodiments, the cement composition comprises Type III Portland cement (e.g., comprising about 57 wt.% C3S, about 19 wt.% C2S, about 10 wt.% C3A, about 7 wt.% C4AF, about 3.0 wt.% MgO, about 3.1 wt.% SO3, and about 1.3 wt.% CaO).

[0097] In some embodiments, the cement composition comprises Type IV Portland cement (e.g., comprising about 28 wt.% C3S, about 49 wt.% C2S, about 4 wt.% C3A, about 12 wt.% C4AF, about 1.8 wt.% MgO, about 1.9 wt.% SO3, and about 0.8 wt.% free CaO).

[0098] In some embodiments, the cement composition comprises Type V Portland cement (e.g., comprising about 38 wt.% C3S, about 43 wt.% C2S, about 4 wt.% C3A, about 9 wt.% C4AF, about 1.9 wt.% MgO, about 1.8 wt.% SO3, and about 0.8% free CaO).

[0099] In some embodiments, the cement composition is less hydrophobic than the biochar. In some embodiments, the cement composition is less hydrophobic than the modified biochar.

[0100] Compositions including cement compositions In some embodiments, a composition according to the present disclosure comprises a cement composition and modified biochar.

[0101] In some embodiments, the composition comprises modified biochar in a range of about 1% to about 20%, about 2% to about 20%, or about 2.5% to about 15% by weight of the combination of the cement composition and the modified biochar. In some embodiments, the composition comprises modified biochar in a range of about 1% to about 3%, about 3% to about 7%, about 8% to about 12%, or about 13% to about 17% by weight of the combination of the cement composition and the modified biochar. In some embodiments, the composition comprises about 1 wt%, about 1.5 wt%, about 2 wt%, about 2.5 wt%, about 3 wt%, about 3.5 wt%, about 4 wt%, about 4.5 wt%, about 5 wt%, about 5.5 wt%, about 6 wt%, about 6.5 wt%, about 7 wt%, about 7.5 wt%, about 8 wt%, about 8.5 wt%, about 9 wt%, about 9.5 wt%, about 10 wt%, about 15 wt%, about 16 wt%, about 17 wt%, about 18 wt%, about 19 wt%, about 20 wt%, about 21 wt%, about 22 wt%, about 23 wt%, about 24 wt%, about 25 wt%, about 26 wt%, about 27 wt%, about 28 wt%, about 29 wt%, about 30 wt%, about 31 wt%, about 32 wt%, about 33 wt%, about 34 wt%, about 35 wt%, about 36 wt%, about 37 wt%, about 38 wt%, about 39 wt%, about 40 wt%, about 40 wt%, about 41 wt%, about 42 wt%, about 43 wt%, about 44 wt%, about 45 wt%, about 46 wt%, about 47 wt%, about 48 wt%, about 49 wt%, about 50 wt%, about 50 wt%, about 51 wt%, about 52 wt%, about 53 wt%, about 54 wt%, about 55 wt%, about 56 wt%, about 57 wt%, about 58 wt%, about 59 wt%, about 60 wt%, about 61 wt%, about 62 wt%, about 63 wt%, about 64 wt%, about 65 wt%, In some embodiments, the composition comprises at least about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7%, about 8%, about 9%, about 10%, about 11%, about 12%, about 13%, about 14%, about 15%, about 16%, about 17%, about 18.5%, about 19%, about 19.5%, or about 20% modified biochar by weight. In some embodiments, the composition comprises at least about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7%, about 8%, about 9%, or about 10% modified biochar by weight. In some embodiments, the composition comprises up to about 20%, about 19%, about 18%, about 17%, about 16%, or about 15% modified biochar by weight.

[0102] In some embodiments, the composition includes water, in a weight ratio to the combination of the cement composition and the modified biochar of about 0.1 to about 10, about 0.1 to about 5, about 0.1 to about 3, about 0.1 to about 1, or about 0.1 to about 0.5.

[0103] In some embodiments, the composition includes fine aggregate (e.g., sand, gravel). In some embodiments, the weight ratio of the combination of the cement composition and the modified biochar to the fine aggregate is in the range of about 1 to about 100, about 1 to about 10, about 1 to about 5, about 1 to about 4, or about 2 to about 3.

[0104] In some embodiments, the method of preparing the composition includes mixing the modified biochar with a cement composition. In some embodiments, the modified biochar and the cement composition are mixed for about 1 minute to about 10 minutes, about 1 minute to about 5 minutes, or about 1 minute to about 3 minutes. In some embodiments, the modified biochar and the cement composition are mixed at a speed in the range of about 10 r / min to about 500 r / min, about 50 r / min to about 500 r / min, or about 100 r / min to about 300 r / min. In some embodiments, the mixing speed may be increased. For example, in some embodiments, the first mixing speed is less than the second mixing speed. In some embodiments, the first mixing speed is in the range of about 10 r / min to about 200 r / min, about 50 r / min to about 200 r / min, or about 100 r / min to about 200 r / min. In some embodiments, the second mixing speed is within the range of about 200 r / min to about 500 r / min, about 200 r / min to about 400 r / min, about 200 r / min to about 300 r / min, or about 250 r / min to about 300 r / min.

[0105] In some embodiments, the method of preparing the composition further comprises adding water to the combination of the modified biochar and the cement composition. In some embodiments, the mixing speed is in the range of about 10 r / min to about 200 r / min, about 50 r / min to about 200 r / min, or about 100 r / min to about 200 r / min.

[0106] In some embodiments, the method of preparing the composition further includes adding fine aggregate (e.g., sand, gravel) to the combination of modified biochar and cement composition. In some embodiments, the fine aggregate is added within a time range of about 10 seconds to about 5 minutes, about 10 seconds to about 1 minute, about 10 seconds to about 45 seconds, about 15 seconds to about 45 seconds. In some embodiments, the mixing speed during the addition of the fine aggregate is substantially the same as the mixing speed during the addition of the water. In some embodiments, mixing may be interrupted to vary the mixing speed. In some embodiments, the mixing speed is increased to a range of about 200 r / min to about 500 r / min, about 200 r / min to about 400 r / min, about 200 r / min to about 300 r / min, or about 250 r / min to about 300 r / min. In some embodiments, the increased mixing speed is maintained for a time in the range of about 10 seconds to about 5 minutes, about 10 seconds to about 1 minute, about 10 seconds to about 45 seconds, about 15 seconds to about 45 seconds. In some embodiments, mixing may be interrupted for a time range of about 10 seconds to about 5 minutes, about 30 seconds to about 3 minutes, or about 30 seconds to about 2 minutes. In some embodiments, mixing may be resumed at a mixing speed in the range of about 200 r / min to about 500 r / min, about 200 r / min to about 400 r / min, about 200 r / min to about 300 r / min, or about 250 r / min to about 300 r / min. In some embodiments, the resumed mixing may be maintained for a time range of about 1 minute to about 5 minutes, about 1 minute to about 3 minutes, or about 30 seconds to about 1.5 minutes.

[0107] Characterization In some embodiments, provided compositions can be characterized, for example, to determine compressive strength. In some embodiments, compositions including modified biochar and cement compositions have a compressive strength (e.g., measured after about 7 days, about 14 days, about 28 days, 35 days, 42 days, or about 56 days of sealed curing) in the range of about 30 MPa to about 70 MPa (e.g., about 30 MPa to about 45 MPa, about 40 MPa, about 35 MPa to about 55 MPa, about 45 MPa, about 45 MPa to about 60 MPa, about 50 MPa, at least 30 MPa). In some embodiments, a composition comprising modified biochar and a cement composition has a lower (e.g., about 1% to about 50% lower, about 1% to about 17% lower, about 1% to about 16% lower, about 1% to about 9% lower, about 1% to about 3% lower, about 1% to about 25% lower, about 1% to about 14% lower, about 1% to about 7% lower, about 1% to about 5% lower, about 1% to about 9% lower, about 1% to about 5% lower, about 1% to about 4% lower) than a cement composition or a composition comprising a cement composition but not modified biochar. low, about 2% to about 17% low, about 2% to about 16% low, about 2% to about 9% low, about 3% to about 25% low, about 3% to about 14% low, about 3% to about 7% low, about 2% to about 21% low, about 2% to about 9% low, about 2% to about 5% low, about 4% to about 21% low, about 8% to about 21% low, about 4% to about 9% low, about 6% to about 25% low, about 13% to about 25% low, about 6% to about 14% low, about 8% to about 17% low, about 8% to about 16% low, about 15% to about 17% low). In some embodiments, compositions comprising a high amount of modified biochar have a lower compressive strength (e.g., measured after sealed curing for about 7 days, about 14 days, about 28 days, 35 days, 42 days, or about 56 days). In some embodiments, compressive strength may be measured according to American Society for Testing and Materials (ASTM) C109 using a common testing machine.

[0108] In some embodiments, the compressive strength of a composition comprising about 1% to about 4% modified biochar by weight is about 1% to about 10% lower than the compressive strength of a cement composition or a composition comprising a cement composition but not modified biochar. In some embodiments, the compressive strength of a composition comprising about 3% to about 7% modified biochar by weight is about 1% to about 10% lower than the compressive strength of a cement composition or a composition comprising a cement composition but not modified biochar. In some embodiments, the compressive strength of a composition comprising about 8% to about 10% modified biochar by weight is about 5% to about 20% lower than the compressive strength of a cement composition or a composition comprising a cement composition but not modified biochar. In some embodiments, the compressive strength of a composition comprising about 13% to about 17% modified biochar by weight is about 10% to about 30% lower than the compressive strength of a cement composition or a composition comprising a cement composition but not modified biochar.

[0109] In some embodiments, provided compositions can be characterized, for example, to determine flexural strength. In some embodiments, compositions including modified biochar and cement compositions have a flexural strength (e.g., measured after about 7 days, about 14 days, about 28 days, 35 days, 42 days, or about 56 days of sealed curing) in the range of about 5 MPa to about 9 MPa (e.g., about 5 MPa to about 7.5 MPa, about 5 MPa to about 7 MPa, about 5 MPa to about 6 MPa, about 6.5 MPa to about 8.5 MPa, about 6.5 MPa to about 7.5 MPa, about 7.5 to about 9 MPa, about 7.5 to about 8.5 MPa). In some embodiments, compositions comprising modified biochar and a cement composition have a lower flexural strength (e.g., about 1% to about 50% lower, about 1% to about 9% lower, about 1% to about 15% lower, about 1% to about 13% lower, about 1% to about 5% lower, about 1% to about 3% lower, about 1% to about 2.5% lower, about 3% to about 9% lower, about 10% to about 15% lower, about 11% to about 15% lower, about 13% to about 15% lower, about 2% to about 13% lower, about 1% to about 4% lower, about 1% to about 3% lower, about 3% to about 13% lower) (e.g., measured after sealed curing for about 7 days, about 14 days, about 28 days, about 35 days, about 42 days, or about 56 days) compared to a cement composition or a composition comprising a cement composition but not modified biochar. In some embodiments, compositions comprising a large amount of modified biochar have a lower flexural strength. In some embodiments, flexural strength may be measured by performing a three-point bending test.

[0110] In some embodiments, the flexural strength of a composition comprising about 1% to about 4% modified biochar by weight is about 1% to about 15% lower than the flexural strength of a cement composition or a composition comprising a cement composition but not modified biochar. In some embodiments, the flexural strength of a composition comprising about 3% to about 7% modified biochar by weight is about 1% to about 15% lower than the flexural strength of a cement composition or a composition comprising a cement composition but not modified biochar. In some embodiments, the flexural strength of a composition comprising about 8% to about 12% modified biochar by weight is about 5% to about 20% lower than the flexural strength of a cement composition or a composition comprising a cement composition but not modified biochar. In some embodiments, the flexural strength of a composition comprising about 13% to about 17% modified biochar by weight is about 10% to about 25% lower than the flexural strength of a cement composition or a composition comprising a cement composition but not modified biochar. Without wishing to be bound to any particular theory, it is possible that the inert nature of the modified biochar and / or its increased porosity may contribute to the reduced flexural strength.

[0111] In some embodiments, provided compositions can be characterized, for example, to determine the amount of heat generated (e.g., per weight of cement composition). In some embodiments, a composition comprising modified biochar and a cement composition has a greater amount of heat generated (e.g., about 1% to 50% greater, about 1% to about 20% greater, about 10% greater) than a cement composition or a composition comprising a cement composition but not modified biochar (e.g., measured after about 7 days, about 14 days, about 28 days, about 35 days, 42 days, or about 56 days of sealed curing). In some embodiments, a composition comprising about 13% to 17% by weight of modified biochar has a greater amount of heat generated than a cement composition or a composition comprising a cement composition but not modified biochar. While not wishing to be bound by any particular theory, it is believed that the increased amount of heat generated is due to the high surface area of ​​the modified biochar providing additional nucleation sites for CSH. In some embodiments, the amount of heat generated can be measured by an isothermal calorimeter.

[0112] In some embodiments, provided compositions can be characterized, for example, to determine chemically bound water (e.g., per weight of cement composition). In some embodiments, a composition comprising modified biochar and a cement composition has chemically bound water (e.g., measured after about 7 days, about 14 days, about 28 days, about 35 days, about 42 days, or about 56 days of sealed curing) in the range of about 6% to about 9% per gram of cement composition and modified biochar. In some embodiments, a composition comprising modified biochar and a cement composition has less chemically bound water (e.g., about 1 to about 50% less) than a cement composition or a composition comprising a cement composition but not modified biochar (e.g., measured after about 7 days, about 14 days, about 28 days, about 35 days, about 42 days, or about 56 days of sealed curing). In some embodiments, chemically bound water can be measured by TGA.

[0113] In some embodiments, provided compositions can be characterized, for example, to determine the relative amount of phase Ca(OH)2. In some embodiments, a composition comprising a modified biochar and a cement composition has Ca(OH)2 (e.g., measured after about 7 days, about 14 days, about 28 days, 35 days, 42 days, or about 56 days of sealed curing) in the range of about 6% to about 9% per gram of cement composition and modified biochar (e.g., about 10% per gram of cement composition and modified biochar). In some embodiments, a composition comprising modified biochar and a cement composition comprises less Ca(OH)2 (e.g., about 1% to about 50% less, about 1% to about 40% less, about 1% to about 30% less, about 5% to about 20% less, about 10% less) than a cement composition or a composition comprising a cement composition but not modified biochar (e.g., measured after about 7 days, about 14 days, about 28 days, about 35 days, about 42 days, or about 56 days of sealed curing). In some embodiments, the relative amount of Ca(OH)2 can be measured by TGA.

[0114] In some embodiments, provided compositions can be characterized, for example, to determine a flow index. In some embodiments, a composition comprising modified biochar and a cement composition has a lower flow index (e.g., about 1% to about 150% lower, about 1% to about 95% lower, about 20% to about 95% lower, about 40% to about 95% lower, about 60% to about 95% lower, about 90% lower, about 30% lower, about 56% lower, about 83% lower, at least 20% lower, at least 40% lower, at least 60% lower, at least 85% lower) compared to a cement composition or a composition comprising a cement composition but not modified biochar. In some embodiments, a composition comprising a high amount of modified biochar has a lower flow index. In some embodiments, the flow index can be measured using the ASTM C1437 standard.

[0115] In some embodiments, the flow index of a composition comprising about 1% to about 4% modified biochar by weight is about 1% to about 50% lower than the flow index of a cement composition or a composition comprising a cement composition but not modified biochar. In some embodiments, the flow index of a composition comprising about 3% to about 7% modified biochar by weight is about 1% to about 75% lower than the flow index of a cement composition or a composition comprising a cement composition but not modified biochar. In some embodiments, the flow index of a composition comprising about 8% to about 10% modified biochar by weight is about 1% to about 95% lower than the flow index of a cement composition or a composition comprising a cement composition but not modified biochar. In some embodiments, the flow index of a composition comprising about 13% to about 17% modified biochar by weight is about 1% to about 95% lower than the flow index of a cement composition or a composition comprising a cement composition but not modified biochar.

[0116] In some embodiments, provided compositions can be characterized, for example, to determine the specific surface area. In some embodiments, a composition comprising a modified biochar and a cement composition has a higher specific surface area (e.g., about 1 to about 50% higher) than a cement composition or a composition comprising a cement composition but not modified biochar.

[0117] In some embodiments, provided compositions can be characterized, for example, to determine water absorption. In some embodiments, a composition comprising modified biochar and a cement composition has lower water absorption (e.g., about 1% to about 100% lower, e.g., about 10% to about 75%) than a cement composition or a composition comprising a cement composition but not modified biochar (e.g., measured after sealed curing for about 7 days, about 14 days, about 28 days, about 35 days, 42 days, or about 56 days). In some embodiments, compositions comprising a higher amount of modified biochar have lower water absorption.

[0118] In some embodiments, the water absorption of a composition comprising about 1% to about 4% modified biochar by weight is about 1% to about 30% lower than the water absorption of a cement composition or a composition comprising a cement composition but not modified biochar. In some embodiments, the water absorption of a composition comprising about 3% to about 7% modified biochar by weight is about 10% to about 65% lower than the water absorption of a cement composition or a composition comprising a cement composition but not modified biochar. In some embodiments, the water absorption of a composition comprising about 8% to about 12% modified biochar by weight is about 30% to about 75% lower than the water absorption of a cement composition or a composition comprising a cement composition but not modified biochar. In some embodiments, the water absorption of a composition comprising about 13% to about 17% modified biochar by weight is about 40% to about 100% lower than the water absorption of a cement composition or a composition comprising a cement composition but not modified biochar.

[0119] In some embodiments, water absorbency can be measured using the ASTM C1585 standard. In some embodiments, water absorbency is determined from weight gain using equation (2).

number

[0120] In some embodiments, provided compositions can be characterized, for example, to determine electrical conductivity. In some embodiments, compositions including modified biochar and cement compositions have electrical conductivity in the range of about 5 to about 30 mS / m (e.g., measured after sealed curing for about 7 days, about 14 days, about 28 days, 35 days, 42 days, or about 56 days). In some embodiments, compositions including modified biochar and cement compositions have higher electrical conductivity (e.g., about 1 to 50% higher) than cement compositions or compositions including cement compositions but not modified biochar. In some embodiments, compositions including a higher amount of modified biochar have higher electrical conductivity (e.g., measured after sealed curing for about 7 days, about 14 days, about 28 days, 35 days, 42 days, or about 56 days).

[0121] In some embodiments, the electrical conductivity of a composition comprising about 1% to about 4% modified biochar by weight is about 1 to about 20% higher than the electrical conductivity of a cement composition or a composition comprising a cement composition but not modified biochar. In some embodiments, the electrical conductivity of a composition comprising about 3% to about 7% modified biochar by weight is about 5 to about 25% higher than the electrical conductivity of a cement composition or a composition comprising a cement composition but not modified biochar. In some embodiments, the electrical conductivity of a composition comprising about 8% to about 12% modified biochar by weight is about 10 to about 40% higher than the electrical conductivity of a cement composition or a composition comprising a cement composition but not modified biochar. In some embodiments, the electrical conductivity of a composition comprising about 13% to about 17% modified biochar by weight is about 10 to about 40% higher than the electrical conductivity of a cement composition or a composition comprising a cement composition but not modified biochar.

[0122] In some embodiments, electrical conductivity can be measured by the two-pole method using commercially available equipment. The resistivity and conductivity of a sample can be calculated using Equations 3 and 4, respectively.

number

number

[0123] In some embodiments, provided compositions can be characterized, for example, to determine piezoresistance (e.g., the composition is characterized as having a linear correlation between applied stress and the rate of change of resistivity (FCR). In some embodiments, the composition comprising the modified biochar and cement composition is piezoresistive. In some embodiments, the correlation between applied stress and FCR is measured using a coefficient of determination (R 2 In some embodiments, the composition comprising modified biochar and cement composition has a coefficient of determination greater than about 0.5 in the correlation between applied stress and percent change in resistivity. In some embodiments, the coefficient of determination for the composition comprising modified biochar in the correlation between applied stress and percent change in resistivity is greater (about 100% to about 500%) than the coefficient of determination for the cement composition or the composition comprising the cement composition but not modified biochar. In some embodiments, the percent change in resistivity (FCR) can be calculated using Equation 5, FCR = (ρ t -ρ0) / ρ0 equation (5) where ρ t is the resistivity at a particular time, and ρ is the initially measured resistivity. In some embodiments, the resistivity may be determined according to Equation 3.

[0124] In some embodiments, a provided composition may be characterized in that it has a self-sensing capability (e.g., the ability of a structural material to sense stress, strain, and / or temperature therein without the incorporation of any external sensors.) In some embodiments, a provided composition is piezoresistive. EXAMPLES

[0125] Example This example describes an exemplary cement composition and modified biochar-containing composition according to the present disclosure. A representative manufacturing process is described below. Those skilled in the art will recognize that the specific conditions and inherent values ​​described herein may be modified as desired.

[0126] Sample preparation In this example, the biochar particles were millimeter-sized on average. The hydrophobicity of the biochar was enhanced following chemical-mechanical modification. To achieve hydrophobicity, the biochar was treated with 4 wt. % stearic acid (C 17 H 35 The biochar was milled in a planetary ball mill with 1,000g of ethanol (CO2H2) for 3 h. Stearic acid acted as a grinding aid, resulting in a very fine particle size distribution of the biochar along with superhydrophobic surface properties (Figure 1). The resulting product after this process is called modified biochar.

[0127] The materials used in this example included ordinary Portland cement (OPC), modified biochar, and river sand. OPC contained 20.1% SiO2, 63.7% CaO, 4.7% Al2O3, 3.5% Fe2O3, and 3.1% SO3. The average particle sizes of OPC and modified biochar were 19.3 μm and 11.7 μm, respectively. The particle size distributions of the materials (shown in FIG. 2) were determined using a laser particle size analyzer, taking into account a refractive index of 1.63.

[0128] The biochar used in this example was produced by pyrolysis of wood chips. The primary product of this process was biofuel, with biochar being a by-product. The resulting biochar was bone dry and stored in a sealed plastic container. Based on CHN analysis, the biochar contained 80.22% carbon, 1.23% hydrogen, and 0.2% nitrogen by weight.

[0129] The modified biochar was used as a partial replacement for OPC to prepare paste and mortar samples for experimental fabrication. The paste samples were used to track the effect of modified biochar on cement composition hydration and microscopic phase formation. The mortar samples were used to track the effect of modified biochar on strength, water absorption and self-sensing properties. In each case, a total of five batches were prepared. The cement replacement levels by modified biochar in these batches were 0% (control batch), 2.5%, 5%, 10% and 15%. In all batches, the water to binder (cement + modified biochar) ratio was 0.42 and the binder to fine aggregate (e.g. sand) ratio was 2.75. To prepare the paste samples, the selected percentage of modified biochar was first mixed (i.e. dry mixed) with OPC for 2 minutes to ensure homogenous distribution of these two materials. Water was then added to the mixture and mixed again for 2 minutes to prepare the paste.

[0130] For mortar sample preparation, the selected percentage of modified biochar and cement content were mixed in a Hobart mixer for 2 min, with the first 90 s at low speed (140±5 r / min) and the remaining 30 s at medium speed (285±10 r / min) to obtain modified biochar powder homogeneously mixed with cement. Mortar samples were then prepared according to the mixing procedure of the ASTM C305 standard. The mixture of cement and modified biochar was first added to the water in a bowl and mixed at a speed of 140±5 r / min. Then, the entire amount of sand was slowly added over 30 s while mixing at the same speed. The mixer was stopped and the speed was changed to medium speed (285±10 r / min), which was then mixed for 30 s. After that, the mixer was stopped again and the mortar was allowed to settle for 90 s. Finally, the mixture was mixed again at medium speed (285±10 r / min) for 60 s.

[0131] Experimental Method Fluidity, compressive strength and bending strength tests To measure the effect of modified biochar on the workability of mortar batches, flow table tests were performed using the ASTM C1437 standard. The compressive strength of 50 mm by 50 mm mortar cubes was determined using a common testing machine at loading rates of 900-1800 N per second (200-400 lb per second) according to ASTM C109. The flexural strength was determined by performing three-point bending tests on girder specimens with dimensions 40 mm x 30 mm x 180 mm. The mortar specimens were tested after sealed curing for 7, 28 and 56 days.

[0132] Effects on cement hydration kinetics and products Paste samples were prepared by mixing water with cement and modified biochar. After mixing, approximately 15 g of paste sample was placed in a glass vial to monitor the heat of hydration. Heat evolution from the cement paste was measured using an isothermal calorimeter (TA Air, TA instrument) at an ambient temperature of 25°C for 100 hours. Thermogravimetric analysis (TGA) was performed on the paste samples to determine the effect of modified biochar on the cement hydration products. Hydration of the cement paste samples was quenched using acetone after sealed curing for 7, 14 and 28 days. The dried paste samples were then ground using a mortar and pestle. Approximately 30-40 mg of powder paste sample was tested per batch. The powder sample was placed in a pan and kept under isothermal conditions at room temperature for 5 minutes. The temperature of the chamber was then increased to 980°C at an increment of 10°C per minute. From this study, the quantitative amount of chemically bound water in calcium silicate hydrate (CSH) and Ca(OH)2 in hydrated cement paste was determined. In addition, Fourier transform infrared (FTIR) spectra were collected to characterize the biochar and cement hydration products. A commercially available Nicolet iS50 FTIR from Thermo Scientific was used for this study. The spectra were collected using attenuated total reflection (ATR) mode with a resolution of 4 cm-1 and 32 scans per sample. Scanning electron microscopy (SEM) images were obtained using a Zeiss-FIB SEM operated in high vacuum mode. The instrument was operated using an accelerating voltage of 25 kV.

[0133] Water absorption rate Water absorption tests of the mortar cubes were performed by modifying the ASTM C1585 standard test method. After 28 days of sealed curing, the mortar cubes were stored in a controlled environment (50% relative humidity [RH] and 50°C) for 3 days. The samples were then kept in a sealed container for another 15 days for stabilization of the internal humidity. After this conditioning period, all sides except the top and bottom of the 50 mm mortar cube specimens were sealed with adhesive tape. The bottom of the mortar cube was then immersed in water (approximate immersion depth = 2.5 mm) and the weight gain of the samples was monitored at regular intervals for up to 9 days. From the weight gain, the water absorption of the samples was determined using Equation 2 above.

[0134] The water absorption rate was calculated as two segments: initial and secondary absorption rates. According to the standard, the initial rate was obtained after the first 6 hours of exposure and the secondary rate was obtained for the remaining period.

[0135] Electrical Conductivity The resistivity and conductivity of the mortar cube samples were measured after 7, 28 and 56 days of sealed curing. The resistance of the samples was measured according to the two-pole method using a commercial device (Giatec RCON). For all batches, a constant weight of 290 grams was applied to the top plate during the measurements using a constant frequency of 600 Hz. The resistivity and conductivity of the samples were then calculated using equations 3 and 4, respectively.

[0136] Self-detection ability Self-sensing refers to the ability of a structural material to sense stress, strain and / or temperature within it without the incorporation of any external sensors. A self-sensitivity test was carried out using a mortar girder specimen with dimensions 40mm x 30mm x 180mm. For this test, a four-electrode Wenner array configuration was prepared using copper plates as shown in Figure 3. Four copper plates were inserted into the poured mortar girder at points A, B, C and D acting as electrodes. The distances AB, BC and CD were 30mm, 60mm and 30mm respectively. The mortar girder was then subjected to a loading rate of 15N / s and a DC voltage of 20V. The current in the specimen was recorded using a NI-9219 Universal Analog Input Module as a data recorder. The resistance was measured from the applied voltage and the recorded current. The percent change in resistivity (FCR) was then determined using Equation 5, whereas the resistivity was calculated using Equation 3.

[0137] Comparison of relative embodied carbon footprints Substituting OPC with modified biochar in cementitious materials reduces the overall OPC consumption and therefore the embodied carbon of the mortar samples. Furthermore, the total carbon content of the biochar used was found to be 80% by weight. The use of biochar in the mortar or paste samples ensures the sequestration of this carbon, which cannot return to the atmosphere. Both factors were taken into account to calculate the relative reduction in carbon footprint due to the use of biochar as a partial replacement for OPC.

[0138] Results and Discussion heat of hydration The heat flow rates of the paste samples per gram of cement and per gram of solids are shown in Figure 4A and Figure 4C, respectively. The main peak in heat flow is associated with C3S hydration to form CSH and Ca(OH)2. From the heat flow plot, it was found that the hydration reaction rate was not reduced or retarded by using modified biochar as a partial replacement for cement. Notably, commercially available permeability reducing admixtures (PRAs) retard the cement hydration reaction. On the other hand, the modified biochar produced in this example showed an increase in the peak heat flow rate per gram of cement, as shown in Figure 4A. The higher slope of the heat flow rate at the initial stage also implies a faster hydration rate with the addition of modified biochar. There was also an almost 10% increase in the total heat generation per gram of cement with the addition of 15 wt% modified biochar content, as shown in Figure 4B. This accelerated hydration was attributed to the nucleation effect (also known as the "filler effect") of modified biochar. As seen in Figure 2, the modified biochar has a finer particle size distribution than OPC. The high surface area of ​​these fine particles provided additional nucleation sites for CSH and therefore accelerated cement hydration. Nevertheless, the peak heat flow and total heat release per gram of solids (i.e., the combined weight of OPC and modified biochar) decreased with increasing modified biochar content, as seen in Figures 4C and 4D, respectively. Such a decrease may be attributed to the reduced amount of cement (reactive raw material) content per gram of solids. As seen in Figures 4E and 4F, this decrease in total heat release or peak heat flow per gram of solids was less than 10%.

[0139] Microscopic phase evaluation Figure 5 shows typical thermogravimetric analysis (TGA) plots of cement paste samples with different modified biochar contents. In this figure, typical cement hydration products, such as CSH gel, ettringite (AFt) and weight loss due to decomposition of Ca(OH)2 are identified based on literature data. In addition to the typical cement hydration products, two unusual peaks were observed around 500 °C and 700 °C in the DTG plot. The first additional peak represents the weight increase of the sample. This peak could be due to the weight increase due to gas adsorption by the biochar particles. The second additional peak could be explained as the release of CO2 due to the oxidation of biochar and the decomposition of CaCO3, which may have been formed due to negligible atmospheric carbon dioxide absorption of the paste samples.

[0140] The TGA data was further analyzed to determine the amount of Ca(OH)2 and chemically bound water present in the hydrated pastes according to previously published procedures. The amount of chemically bound water could be evaluated to compare the extent of cement hydration. Figure 6A shows the amount of chemically bound water per gram of cement with different modified biochar contents. Figure 6A shows that when 2.5%, 5% and 10% of the cement was replaced with modified biochar, the chemically bound water decreased by 6.5%, 3.2% and 5.6%, respectively, after 7 days of curing. On the other hand, when 15% of the cement was replaced with modified biochar, the chemically bound water increased by 5% after 7 days of curing, which supports a 10% increase in the total heat of hydration (per gram of cement). Thus, this result provides further evidence that the modified biochar particles act as seeds to accelerate cement hydration, i.e., the filler effect, due to their fineness compared to the cement particles. However, after longer curing durations (e.g., 14 and 28 days), the control batches contained higher amounts of chemically bound water compared to the modified biochar batches. The reduction in chemically bound water with the addition of 10% modified biochar was only 9% and 15% after 14 and 28 days of curing, respectively. Figure 6B shows the variation in calcium hydroxide with different modified biochar contents. The relative amount of Ca(OH)2 decreased with increasing modified biochar content. This trend may have been caused by the decrease in the amount of OPC with increasing modified biochar content. Nevertheless, the reduction in Ca(OH)2 was near 10%, suggesting that such an effect of modified biochar on the hydration products was not significant.

[0141] ATR / FTIR spectra of modified biochar and cement paste Figure 7A shows a comparison between untreated and modified biochar. -1 The broad peaks around 2925 and 2850 cm of the modified biochar were due to hydroxyl groups. -1The peaks around 1600 cm were asymmetric and symmetric alkyl CH groups, respectively. These peaks were not present in the untreated biochar. -1 The C=C stretching vibration of aromatic groups near 1000 cm was stronger in the modified biochar. -1 The asymmetric stretching of the CCO carbonyl group near 1463–2000 cm was stronger in the modified biochar than in the untreated biochar. -1 , and 3500-3900 cm -1 The small, weak peak in the range of 0.1% may be due to carbonate formed due to the reaction of biochar with CO2 in the presence of moisture.

[0142] FIG. 7B shows the effect of biochar inclusion in the cementitious matrix. -1 and 1410cm -1 The wave numbers around 2- Out-of-plane bending vibration of CO3 2- This was due to the asymmetric vibration of 1639cm. -1 The bending peak at 950 cm was due to chemically bound water and Ca(OH)2. The FTIR plot suggested the hypothesis that the hydration products were not changed by the inclusion of biochar. -1 The bands of CSH gel can be seen in the upper part of the spectrum. The bands of silica gel polymerization at higher wavenumbers (1100 cm -1 ) was also the same in all batches. Most of the biochar peaks overlapped with the cementitious reaction products.

[0143] Workability The effect of modified biochar on the workability of the mortar samples was determined using flow table tests. The flow index of the mortar samples shown in Figure 8 was found to decrease with increasing modified biochar content. The flow index of the 15% modified biochar batch was found to be 90% lower than the control batch. The reduction rates of the other batches were around 30%, 56% and 83% at 2.5 wt%, 5 wt% and 10 wt% modified biochar contents, respectively. This decrease in workability due to the addition of modified biochar could be attributed to two aspects. First, the particle size of modified biochar is smaller compared to OPC. Therefore, the specific surface area of ​​the mixture could have been increased by replacing OPC with modified biochar. The high surface area could have increased the friction level leading to lower workability. Second, due to hydrophobicity, modified biochar particles could have repelled water molecules. Such repulsive force could have contributed to the decrease in workability of the mortar mixture.

[0144] Compressive and bending strength The compressive strength of the mortar samples was found to decrease with increasing modified biochar content in the mixture, as shown in Figure 9A. Such decrease in compressive strength may be caused due to the inert nature of modified biochar. The compressive strength of the control batch was found to be 43 MPa after 7 days of curing. The decrease in compressive strength with the addition of modified biochar content of 2.5%, 5%, 10% and 15% was 3.0%, 4.6%, 8.6% and 20.0%, respectively. These decrease levels were 2.9%, 8.8%, 15.6% and 16.5%, respectively, after 56 days of sealed curing. The trend was similar in the bending strength of the mortar beams containing modified biochar as a partial replacement for OPC, as shown in Figure 9B. After hydration for 28 days, the flexural strength of the samples decreased by 10.4%, 11.6%, 13.3%, and 14.4% with the addition of 2.5%, 5%, 10%, and 15% modified biochar content, respectively. The decrease in strength due to the addition of modified biochar can be explained by two mechanisms: (i) the inert nature of modified biochar and (ii) the increased porosity. Due to the inert nature of modified biochar, the replacement of cement with this material reduced the relative amount of binding phase in the hydrated paste and mortar systems compared to the control batches. Specifically, the TGA plots shown in Figures 6A and 6B showed that the addition of modified biochar reduced the amount of both Ca(OH)2 and CSH per gram, which are the major binding phases. Therefore, this reduced relative amount of binding phase may have led to the decrease in strength in the case of modified biochar-containing mortar batches. Furthermore, biochar particles generally have higher porosity, which may increase the overall porosity of the cement paste. SEM images of cement paste with 15% modified biochar after 28 days of curing are shown in Figure 10A-C. As can be seen from these figures, the addition of modified biochar introduced organized porosity into the cement paste matrix. Furthermore, wood cell structures were visible in some of the pores, as shown in Figure 10C.

[0145] The compressive and flexural strength results were analyzed using the statistical method of two-sample t-test to identify the significant effect of adding modified biochar. The mean and standard deviation of compressive strength for different cement replacement levels and after different curing durations were compared. The test was performed at the 95% confidence level. Thus, from the statistical analysis, a p-value greater than 0.05 indicated no significant difference in the compared mean strengths and vice versa.

[0146] From Table 1, it can be seen that the addition of 2.5% modified biochar has no significant effect on the compressive strength of the mortar. On the other hand, the effect of 5% modified biochar on the compressive strength remained insignificant up to 28 days of curing length. After 56 days of curing, the addition of more than 2.5% modified biochar significantly reduces the compressive strength of the mortar batch. Conversely, after the same curing duration, the addition of modified biochar up to 10% does not significantly affect the flexural strength of the mortar batch. Thus, the adverse effect of modified biochar addition was more pronounced in the case of compressive strength compared to flexural strength. [Table 1]

[0147] Water absorption The water absorption by the mortar samples with respect to the exposure duration is shown in Figure 11A. The addition of modified biochar reduced the water absorption of the mortar samples. After the entire exposure duration, the total water absorption by the samples containing 15% modified biochar was 68% lower than the control batch. This water absorption data was further used to calculate the initial and secondary water absorption by the mortar samples, as shown in Figure 11B and C. In both cases, the 15% modified biochar batch showed the lowest level of water absorption. The reduction in the initial and secondary water absorption with the use of 15% modified biochar was near 70% and 60%, respectively. The reduction in water absorption with the addition of modified biochar could have been due to the fine particle size of modified biochar and the hydrophobic nature of these particles. Therefore, it appears that modified biochar acted as a hydrophobic pore blocking additive in these mortar samples to reduce the moisture permeability.

[0148] Electrical Conductivity The electrical conductivity of mortar samples containing modified biochar was obtained using the two-electrode method. As shown in Figure 12, increasing the biochar content increased the electrical conductivity of the mortar samples. The addition of 15% modified biochar (by mass) increased the electrical conductivity by 28% after 28 days of hydration compared to the control batch. This may be because biochar has a high carbon content that acts as a conductive inclusion in the matrix. Most previous studies have utilized carbon fibers to enhance the electrical conductivity of cement-based composites. A.Belli,et al.,“Evaluating the self-sensing ability of cement mortars manufactured with graphene nanoplatelets,virgin or recycled carbon fibers through piezoresistivity tests,”Sustain.,vol.10,no.11,2018. The carbon content of carbon fibers ranges from 95% to 100%. F.Rajabipour,et al.“Electrical conductivity of drying cement paste,”Mater.Struct.Constr.,2007. The high aspect ratio of carbon fibers also enhances electrical conductivity by creating a uniform network. Although the modified biochar contains a lower amount of carbon with a lower aspect ratio, the addition of this material also ensured a higher electrical conductivity of the mortar samples, as can be seen in this experiment. This may be because the content used in the matrix in previous studies was significantly higher (up to 15 wt%) compared to the usual application amount of carbon nanofibers used in cementitious matrices (around 1%). The application amount of carbon nanofibers is generally limited due to its high cost, poor dispersibility, and its negative effect on the workability of cementitious composites. In the case of previous studies, such shortcomings can be avoided. Thus, previous studies used a higher application amount (15% in this study) to obtain electrical conductivity of cementitious composites comparable to that obtained using carbon nanomaterials.

[0149] The electrical conductivity of the mortar batches was observed to decrease with increasing curing duration. The electrical resistivity and conductivity of cementitious materials are also affected by porosity and intrapore solutions, with higher porosity tending to result in lower electrical resistivity. The degree of hydration of cement increased with increasing curing duration resulting in pore densification due to the formation of hydration products. Thus, as seen in Figure 12, the resulting pore blocking of these hydration products results in a decrease in the electrical conductivity of the mortar samples with increasing curing duration. The electrical conductivity results were analyzed using the statistical method of two-sample t-test to identify the significance of adding modified biochar. As can be seen from Table 2, the addition of modified biochar significantly increases the electrical conductivity of the mortar independent of the dosage used. [Table 2]

[0150] Self-detection ability Self-sensing cementitious composites allow the determination of stress and strain in the matrix by measuring the rate of change of resistivity (FCR). In this experiment, these FCRs were measured when mortar girder specimens were subjected to three-point bending conditions. The good correlation between stress level and FCR suggests a strong self-sensing ability of the composite. The correlation between FCR and stress is generally expressed as (generally R 2 The correlation between stress and FCR was assessed by comparing the coefficient of determination (known as the R value). Figures 13A-B show the correlation between stress and FCR for the two sample batches. For the control batch, the FCR and stress data points appear to be scattered, indicating that there is no direct correlation between these values ​​(low R 2 values) were found, thereby confirming the poor self-sensing ability of the hydrated OPC mortar without any conductive additive (control batch). Nevertheless, after the addition of 15% modified biochar, the variation in stress and FCR increased to R values ​​close to 1. 2Thus, in this batch, the stress could be determined by measuring the resistivity (i.e., FCR), and thus, the addition of modified biochar clearly enhanced the self-sensing ability of this mortar batch. Such a correlation was established in all mortar batches, and the obtained R 2 The values ​​are shown in Table 3. As can be seen, even at 2.5% modified biochar content, there is a high R (above 0.9). 2 These findings indicate that biochar can be an alternative to costly carbon nanomaterials in producing cementitious materials with high electrical conductivity that can be used as self-sensing composites. [Table 3]

[0151] Relatively inclusive carbon The modified biochar can help to reduce the embodied carbon of the cementitious composites by reducing the amount of OPC used in the preparation of these samples and by sequestration of the carbon present in the biochar. The average fixed carbon content of the biochar was 80.22 wt% according to the CHN results. The fixed carbon was then used to calculate the equivalent amount of CO2 stored in the samples due to the addition of biochar. As can be seen from Figure 14A, the addition of around 15% modified biochar is equivalent to around 30 wt% CO2 sequestration in the cement paste. The simplified embodied carbon (eCO2) of the binder mix (cement + modified biochar) was then calculated considering the control batch as the baseline. The embodied carbon of stearic acid was ignored considering that only a small amount of this raw material was used in the production of the modified biochar. The relative embodied carbon (eCO2) of the binder mix calculated according to this methodology is shown in Figure 14B. Based on this approach, the embodied CO2 of the binder mix (i.e., OPC + modified biochar) can be reduced by 10%, 20%, 39% and 59% compared to the control batch by replacing 2.5%, 5%, 10% and 15% by weight of cement with modified biochar, respectively. This reduction in embodied carbon by the addition of 15% modified biochar translates to a reduction of 29% and 10% in the paste and mortar samples, respectively. Thus, these findings indicate that it is possible to produce cementitious composites with a relatively lower carbon footprint by using modified biochar as a partial replacement for cement.

[0152] Environmental importance The development of environmentally friendly and durable cementitious composites for a sustainable future is of great importance. Especially considering the high carbon footprint and energy intensive production of OPC, techniques to reduce the consumption of this cement can effectively contribute to the sustainability of urban infrastructure. This example showed that biochar, a relatively low-cost additive, can play a key role in this case. One of the surprising findings of this study was the relative amount of CO2 sequestration in cementitious composites using biochar. In addition, this example also provided experimental evidence that modified biochar can be used to significantly reduce the water absorption of mortar (up to 70%). Thus, the provided compositions can potentially be used to significantly improve the durability performance of cement-based materials, specifically those related to the permeation of dissolved ions in the matrix, including chloride salt and sulfate permeation. This durable matrix can lead to an extended service life of structural components manufactured using biochar, which in turn can lead to further reduction in cement consumption over time. Due to the high carbon content of biochar, modified biochar can also be used as an electrically conductive inclusion to produce electrically conductive cementitious composites, which can further be used as self-sensing structural elements. However, the addition of modified biochar can negatively affect the compressive and flexural strength of mortar samples. Even though the strength is reduced, the addition of modified biochar successfully introduced multifunctionality into the cementitious composition, including low water absorption, high electrical conductivity, and low carbon footprint. Therefore, if multifunctionality is the desired performance, this reduction in strength can be overcome by adjusting the mix ratio (i.e., lowering the w / c or using supplementary cementitious materials).

[0153] Equivalent Those skilled in the art will recognize, or be able to ascertain using no more than routine experimentation, many equivalents to the specific embodiments of the invention described herein. The scope of the present invention is not intended to be limited to the above Description, but is as set forth in the following claims.

Claims

1. 1. A composition comprising: at least one cement composition; Biochar and modified biochar containing hydrophobic agents The composition comprising:

2. 10. The composition of claim 1, wherein the modified biochar is more hydrophobic than the biochar.

3. The composition of claim 1 , wherein the composition is piezoresistive.

4. 10. The composition of claim 1, wherein the composition comprises the modified biochar in the range of 1% to 30% by weight of the combination of the cement composition and the modified biochar.

5. The composition of claim 1 , wherein the hydrophobic agent is selected from the group consisting of stearic acid, oleic acid, myristic acid, and combinations thereof.

6. 2. The composition of claim 1, wherein the mass ratio of the hydrophobic agent to the biochar is in the range of 1:100 to 1:

10.

7. The composition of claim 1 further comprising water.

8. 8. The composition of claim 7, wherein the mass ratio of the water to the combination of the cement composition and the modified biochar is from 0.25 to 0.

8.

9. The composition of claim 1 further comprising fine aggregate.

10. 10. The composition of claim 9, wherein the mass ratio of the combination of the cement composition and the modified biochar to the fine aggregate is 2 to 3.

11. The composition of claim 1 , wherein the composition has a lower compressive strength compared to the cement composition.

12. The composition of claim 1 , wherein the composition has a lower flexural strength compared to the cement composition.

13. The composition of claim 1 , wherein the composition has a higher heat release rate than the cementitious composition.

14. The composition of claim 1 , wherein the composition contains less chemically bound water compared to the cementitious composition.

15. The composition contains less Ca(OH) than the cement composition. 2 The composition of claim 1 comprising:

16. The composition of claim 1 , wherein the composition has a lower flow index compared to the cementitious composition.

17. The composition of claim 1 , wherein the composition has a lower water absorption rate compared to the cement composition.

18. The composition of claim 1 , wherein the composition has a higher electrical conductivity than the cement composition.

19. 2. The composition of claim 1, wherein the average size of the modified biochar is in the range of 1 to 50 μm.

20. 2. The cement composition of claim 1, wherein the average size of the cement composition is in the range of 1 to 50 μm.

21. 10. The composition of claim 1, wherein the modified biochar comprises carbon, hydrogen and nitrogen.

22. The composition of claim 1 , wherein the composition is a paste or mortar.

23. 1. A method comprising: preparing a modified biochar by mixing the biochar with a hydrophobic agent, wherein the modified biochar is more hydrophobic than the biochar; combining a cement composition with the modified biochar to form a composition; The method comprising:

24. 24. The method of claim 23, wherein the biochar is prepared by pyrolysis of wood chips.

25. 25. The method of claim 24, wherein the hydrophobic drug is mixed after the pyrolysis.

26. 24. The method of claim 23, wherein the biochar is pulverized in the presence of the hydrophobic agent.

27. 24. The method of claim 23, wherein the mass ratio of the hydrophobic agent to the biochar is in the range of 1:100 to 1:

10.

28. 24. The method of claim 23, wherein the biochar is pulverized by using a mortar and pestle.

29. 24. The method of claim 23, further comprising adding water to the composition.

30. The method of claim 23 , wherein the composition is piezoresistive.

31. 24. The method of claim 23, wherein the composition comprises the modified biochar in the range of 1% to 30% by weight of the combination of the cement composition and the biochar.

32. 24. The method of claim 23, wherein the hydrophobic agent is selected from the group consisting of stearic acid, oleic acid, myristic acid, and combinations thereof.

33. 24. A composition produced by one or more of the methods of claim 23.

34. 1. A method for producing mortar for use in construction, comprising the steps of: preparing biochar using pyrolysis; preparing a modified biochar by mixing the biochar with a hydrophobic agent, wherein the hydrophobic agent comprises stearic acid and the modified biochar comprises 2% to 20% by weight of the hydrophobic agent, and preparing the modified biochar comprises pulverizing the biochar and the hydrophobic agent; combining a cement composition with the modified biochar to create a binder, wherein the modified biochar comprises 1% to 30% by weight of the combination of the cement composition and the modified biochar; adding water to the binder in a weight ratio of the water to the binder of 0.25 to 0.8; adding fine aggregate to the binder in a weight ratio of the fine aggregate to the binder of 2 to 3; mixing the water, the fine aggregate, and the binder to produce the mortar; The method comprising:

35. 35. The method of claim 34, wherein the method comprises pulverizing the biochar and the hydrophobic agent for a period of between 1 hour and 5 hours.

36. 1. A mortar for use in construction comprising: at least one cement composition; A modified biochar comprising biochar and a hydrophobic agent, wherein the hydrophobic agent comprises stearic acid, the modified biochar comprises 2% to 20% by weight of the hydrophobic agent, the average size of the modified biochar is in the range of 1 to 50 μm, and the modified biochar comprises 1% to 10% by weight of the total weight of the combination of the at least one cement composition and the modified biochar; Water and wherein the mortar is characterized in that the composition is piezoresistive and the composition is characterized in that the composition has a water absorption rate that is 1% to 90% lower than the at least one cement composition.